Knowledge integration of stakeholders into bio-physical process modelling for regional vulnerability assessment - Hermine Mitter; Mathias Kirchner; Erwin Schmid; Martin Schönhart (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2013)
Climate change affects agriculture differently due to the heterogeneity in bio-physical and economic conditions in Austria. Therefore, stakeholder and expert knowledge is required in regional vulnerability assessments to address region specific challenges and develop compatible adaptation strategies. In a transdisciplinary research project, a working group consisting of regional stakeholders and agricultural experts identified the effects of uncertain future precipitation on soil water erosion as well as the effectiveness of selected soil conservation measures as the most crucial knowledge gap. Consequently, potential sediment losses on cropland have been simulated with the RUSLE (Revised Universal Soil Loss Equation) methodology for several climate change scenarios using the bio-physical process model EPIC (Environmental Policy Integrated Climate) in an Austrian alpine foreland region. The model predicts an increase in sediment yield with higher precipitation sums for 2040 on average. However, reduced tillage and cultivating winter cover crops have been identified as effective adaptation options. The stakeholders have provided local knowledge in crop management and validated the model results according to their clarity, comprehensiveness, and meaningfulness. They confirmed its usefulness to inform farmers and support the public debate on regional climate change adaptation in agriculture.
Keywords: Q18; 300; transdisciplinary regional vulnerability assessment; soil water erosion; EPIC; soil conservation measures; Austria